(untitled) (Historia, 2021)
The Great War of 1914, and the increase in the South African urban society, served as a catalyst to expand the South African social dancing scene. While dancing before the War was still very exclusive, dancing during War time became radically more popular with fund raising balls, the celebration of victories and the infiltration of the jazz beat into ballroom dances. Dancing during this time was however far more than a mere "antidote to war depression", it was the opening up of the public dance sector with the incorporation of the untraditional, dances that turned the dance movements into "dance crazes". This subsequently allowed those that were previously excluded from this elitist past time, to be included into the dance crazes of the time. Die Eerste Wêreldoorlog, en die uitbreiding van stedelike Suid-Afrikaanse gemeenskappe, het gedien as katalisator vir die ontwikkeling van sosiale dans in Suid-Afrika. Voor die Oorlog was dans grootliks as eksklusief beskou, terwyl dit gedurende die Oorlog aansienklik meer gewild geraak het te danke aan fondsinsamelingsdinees, partytjies ter viering van oorwinnings en die insluiting van die jazz ritme in sosiale danse. Dans gedurende hierdie periode was tog veel meer as ’n blote "teëvoeter vir Oorlogsdepressie", dit was inderwaarheid ’n radikale uitbreiding van die publieke danssektor: nie-tradisionele danse wat dans bewegings in meesleurende tendense laat ontaard het. Gevolglik kon diegene wat voorheen uitgesluit was deur die eksklusiewe aard van dans as tydverdryf, meemaak in gewilde dans tendense.